2001
DOI: 10.1007/s001980170122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Season and Vitamin D Supplementation on Bone Mineral Density in Healthy Women: A Double-Masked Crossover Study

Abstract: Vitamin D status is known to be an important determinant of bone mineral density (BMD). There is a significant seasonal variation in serum vitamin D, and some studies have reported an associated seasonal variation in BMD. The present study was devised to investigate whether a seasonal variation in BMD could be detected in healthy normal subjects, along with associated variations in serum parathyroid hormone (PTH), intestinal calcium absorption and biochemical markers of bone turnover. A second aim was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…Our results are consistent with those of Patel et al [23], Harris & Dawson-Hughes [8], who marked similar changes in S-25-OHD concentrations in groups receiving 10 g and 20 g vitamin D 3 /d. Yet, some studies [24 -27] have reported greater increments which refer to stronger response to supplementation.…”
Section: Is a Plateau In The S-25-ohd Concentration Reached?supporting
confidence: 95%
“…Our results are consistent with those of Patel et al [23], Harris & Dawson-Hughes [8], who marked similar changes in S-25-OHD concentrations in groups receiving 10 g and 20 g vitamin D 3 /d. Yet, some studies [24 -27] have reported greater increments which refer to stronger response to supplementation.…”
Section: Is a Plateau In The S-25-ohd Concentration Reached?supporting
confidence: 95%
“…In the present study, no changes were detected in serum PTH levels in subjects who were treated with 600 mg/d elemental calcium and 800 IU/d cholecalciferol. Patel et al [24] examined the effect of cholecalciferol on bone metabolism in healthy adult women who ranged in age from 23 to 70 years (mean age 45.3 years). The results revealed that supplementation with 800 IU/d cholecalciferol for 12 months increased serum 25(OH)D levels, whereas no effects on serum PTH or bone turnover marker levels were detected.…”
Section: Discussionmentioning
confidence: 99%
“…The best clinical indicator of this vitamin status is the serum 25(OH)D 3 level which varies inversely with PTH (parathyroid hormone) levels [7]. Patel et al [8] demonstrated a highly significant seasonal effect on 25(OH) 2 D 3 concentrations but not on BMD and PTH. To our knowledge, only one study has been reported on the vitamin D status in the phase of early postmenopausal bone loss [9].…”
Section: Introductionmentioning
confidence: 99%